Topografia da artéria hepática no fígado de capivara (Hydrochaerus hydrochaeris) - Souza, Wilson Machado de [UNESP]; Souza, Nair Trevizan Machado de [UNESP]; Carvalho, Roberto Gameiro de [UNESP]; Correa, Cláudia Neves [UNESP] (Universidade Federal de Santa Maria (UFSM), 2007)
A distribuição dos ramos da artéria hepática, no fígado, foi estudada em 30 fígados de capivara (Hydrochaerus hydrochaeris) mediante injeção arterial com látex natural corado, fixação em formol a 10%, dissecção pela face visceral e esquematização. A lobação do fígado, nestes animais, é semelhante à do suíno, permitindo identificar os lobos lateral direito, medial direito, quadrado, medial esquerdo, lateral esquerdo e caudado (processos caudado e papilar). A artéria hepática divide-se mais freqüentemente (73,3%) nos ramos direito e esquerdo e, em menor número de preparações (26,6%), trifurca-se nos ramos direito, intermédio e esquerdo. Esses vasos alcançam, sob diferentes arranjos, os lobos do fígado.

The distribution of the hepatic arterial branches in capybara's (Hydrochaerus hydrochaeris) liver was studied in 30 animals. After arterial injection with stain natural latex, the organs were fixed in formaldehyde 10%, dissected and schematized. The lobation of the liver in these animals, is similar to the one of the swine, allowing to identify the following lobes: right lateral, right medial, quadrate, left medial, left lateral and caudate (processes caudate and papillary). The hepatic artery is divided more frequently (73.3%) in the branches right and left and in lesser number of preparations (26.6%), the vessel gives three resulting in the branches right, intermediate and left. These vessels reach, under different arrangements the lobes of the liver, when appears coincident passages with the one of the biliferous ways and portal vein, allowing in this way establish an port-bilio-arterial division.
Arrangement of hepatic artery in capybara (Hydrochaerus hydrochaeris)
Keywords: fígado; capivara; artéria hepática; roedor; anatomia; liver; capybara; hepatic artery; rodent; anatomy